THE ANNUAL CYCLE IN THE TESTIS OF FRESHWATER CATFISH CLARIAS MACROCEPHALUS (GUNTHER) - Mollah, M F A (Indian Journal of Fisheries, 2011)
The cyclic changes in the testis of freshwater catfish, Clarias macrocephalus (Gunther) over aperiod of 12 months (August, 1979 to July, 1980) were studied histologically. The six histologicalstages identified in the testis were related to six morphologically determined maturity stages. Spawningtakes place twice a year; in late September to early November and again in March till early June.